Three-Dimensional Simulation and Visualization of Crane Assited Construction Erection Processes - Kang, S.; Chi, Hung-Lin; Miranda, E. (American Society of Civil Engineering, 2009)
Abstract: A system for three-dimensional simulation and animation of erection processes is presented. The system is aimed at providingdetailed planning and visualization in a virtual construction environment as well as for assisting crane operators in real-time duringerection. In the system, construction cranes are modeled and treated as robots in which the motion required for each degree of freedomof the crane is computed as a function of the path to be followed by each component being erected. The sequence and path of eachcomponent are computed such that construction times are minimized and collisions with previously erected components are avoided. Aphysics-based simulation and animation of crane motions was also developed to visualize vibrations induced by crane motion. A specialemphasis is placed on crane maneuvering required for containing motion-induced vibrations at acceptable levels and for increasing safetyat job sites. Examples of the erection of steel and precast reinforced concrete buildings using tower cranes and crawler cranes are included.The system is a significant step forward in computer-assisted construction erection, for both prior to and during construction.